A case study on the experiences of public special education teachers in the first district of Manila: a video production - Leonardo, Ryan Mark I.; Reniedo, Mariz R. and Sun, Jearie Paul J. 4 0 16; 5
ABSTRACT Lower education is a major barrier to the persons with disabilities to experience enrichment and proper education opportunities. The lack of financial support to the persons with disabilities and other social services that would cater to their needs and the common behaviors or beliefs toward education for persons with disabilities, are mutual causes why education is considered in the World Report on Disability of 2011 by the World Health Organization as a disabling barrier to the persons with disabilities. This study was pursued to explore the experiences of the Public Special Education teachers in the First District of Manila. The five selected case studies were teachers who have at least four (4) years of teaching experience, have handled 50 SPED students or more in their service for the SPED program and at least a satisfactory or higher performance rating assessed by a legitimate SPED Center supervisor. Through the interviews, the researchers specifically gathered data on their socio-demographics, their working condition in terms of compensation and benefits, workload and schedule, and teaching materials, their voluntary efforts and their motivations and goals as a SPED teacher. These were the parameters utilized by the researchers in coming up with the video documentary. Upon finishing this study, the researchers have proven that there are struggles and problems in the Special Education program in the Jose Rizal Elementary School.
Undergraduate Thesis: (Bachelor of Mass Communication)) Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2